Political Communications in the Public Sphere Student Protest in Indonesia 2019-2020 - Erik Ardiyanto (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
The government and the parliament have decided to pass problematic bills, such as the Corruption Eradication Commission Bill (RUU KPK), the Criminal Code Bill (RUU KUHP), and the Omnibus Law (RUU Cipta Kerja) into laws. The reasons behind the passage of the bills irto laws are to make bureaucracy easier and facilitate foreign investment inflows to Indonesia. However, the decision-making process failed to involve elements of the community, such as academics, workers, working class, press, and related stakeholders. Consequently, students staged rallies to protest against the passage of the bills into laws in 2019 – 2020. This researchuses an approach qualitative methodology with a critical paradigm. The goal of critical theory is to change a reality that is always unbalanced and dominated.This research tries to encourage change towards a better society and emancipations. The data analysis technique comprises analysis of information sources from the mass media and analysis of research documents. The results of this study find that students had two strategic political communications during the protest. First, the social media movement sent hash tagged messages such as #Reformasidikorupsi #Gejayanmemangil and #Mositidakpercaya. Second, student staged demonstrations in front of the Presidential Place and the House of Representatives Building. When the government and parliament conspire  with oligarchs to make policies to maintain power, then  conflicts of interest with society, and  student protests will be inevitable.  As a result, the students have declared a motion of no confidence for parliament in a non-parliamentary participatory democratic system.